PENGARUH PENGUMUMAN DEVIDEN TUNAI DITINJAU DARI KENAIKAN DAN PENURUNAN DEVIDEN TERHADAP HARGA SAHAM DI BURSA EEFEK INDONESIA - Wibowo, Wisnu Prasetyo; Sulistiyani, Tina (Jurnal Fokus Manajemen Bisnis, 2013)
The purpose of this study is to prove whether there is an influence of increasing and decreasing dividend announcements towards stock prices fell in the days before the announcement of cash dividends with the days after the announcement of cash dividend. This research was conducted on banking companies listed in Bursa Efek Indonesia (BEI) with using purposive sampling technique. The researcher takes 7 companies to be the sampe, that are 2 companies in increasing dividends namely Bank Bumi Artha Tbk, and Bank CIMB Niaga Tbk, and 5 companies for decreasing dividends namely the Bukopin Tbk, Bank Dananmon Indonesia Tbk, Bank Himpunan Saudara 1906 Tbk, Bank Internasional Indonesia Tbk, Bank Rakyat Indonesia Tbk, then testing the hypothesis using a paired t test (Paired Two Sample). Companies that increase the vaue of dividends that the Bank Bumi Artha Tbk and Bank CIMB Niaga Tbk, thereis a significance between the stock price in the days before the announcement of cash dividends with the days after the announcement of cash dividends, while companies that reduced the value of dividends, there are two different result test, the first on Bukopin Tbk, Bank Danamon Indonesia Tbk, Bank Himpunan Saudara 1906 Tbk there is a significant differences between the stock price in the days before the announcement of cash dividends with the days after the announcement that the second cash dividends of Bank Internasional Indonesia Tbk, and Bank Rakyat Indonesia Tbk, there is no significant difference between the stock price in the day before the announcement of cash dividens with the dats after the announcement of cash dividends.